Extreme Networks Announces Commitment to Reference Design for SDN Switch Leveraging OpenFlow to Increase Data Center, Campus Network Efficiency: Company Extends Open Fabric Campus to Cloud Vision for Open networking via Big Switch Networks 'Switch Light' OpenFlow Thin Switching Software Platform (PR Newswire, 2013)
Because such statements deal with future events, they are subject to risks and uncertainties, including network design and actual results of use of the product in different environments.